AB0831 PERSPECTIVE ON THE CLINICAL PRACTICE MANAGEMENT OF HYPOVITAMINOSIS D FROM A MEETING OF ITALIAN EXPERTS. (June 2019) - Giollo, Alessandro; Viapiana, Ombretta; Fassio, Angelo; Bertoldo, Francesco; Braga, Vania Teresa; Brandi, Maria Luisa; Calvieri, Stefano; Cianferotti, Luisella; Colao, Annamaria; D'amelio, Patrizia; Mario, Giovanni; Esposti, Luca Degli; et al.
Abstract : Background: Scientific interest in the clinical aspects surrounding vitamin D has increased exponentially in recent years. Unfortunately, this interest is not currently associated with a proportional level of consensus. Indeed, the large number of studies in this field, which are often of low quality and secondary importance has confused even experts and driven them towards controversial positions. Objectives: To shed light on this topic, we arranged a meeting with the aim of collecting the opinions of 50 experts in different specialties ("D..Battito Group"), including internists, endocrinologists, rheumatologists, pediatricians, geriatricians, dermatologists, gynecologists and nephrologists. This meeting dealt with specific questions regarding the management of hypovitaminosis D and aimed to investigate the opinions of Italian experts on this topic. Six key questions were addressed in the meeting. Methods: After a short lecture and a 30 minutes discussion, all the experts expressed their opinions, which were recorded together with any specific commentary. Results: The results of the meeting demonstrated the presence of insufficient agreement on many key questions regarding the management of vitamin D deficiency, even among clinical experts. Conclusion: We hope that the various scientific societies will recognize and analyze the inconsistencies in their own positions and reach adequate consensus, especially on the tenets required for conducting proper and useful investigations on the topic, and that the results of these future new studies will be able to shed the needed light. Acknowledgement: Abdel Jaber M, Benini C, Boner A, Bortolotti R, Brigo M, Catalano A, Ferlin A, Girasole G, Idolazzi L, Lello S, Maestri E, Martinis F, Muratore M, Olivari F, Peroni D, Romagnoli E, Ruggiero C, Saviola G, Sella S, Sfrappini M, Silveri F, Vantaggiato E, Venturin A, Zuccaro C. Disclosure of Interests: Alessandro Giollo: None declared, Ombretta Viapiana Speakers bureau: Novartis, Abbvie, Eli-Lilly, Sanofi Genzyme, Angelo Fassio Speakers bureau: Abiogen Pharma, Francesco Bertoldo: None declared, Vania Teresa Braga: None declared, Maria Luisa Brandi: None declared, Stefano Calvieri: None declared, Luisella Cianferotti Speakers bureau: Abiogen Pharma, Bruno Farmaceutici, Shire, Annamaria Colao: None declared, Patrizia D'Amelio: None declared, Giovanni Mario D'Avola: None declared, Luca Degli Esposti: None declared, Bruno Frediani: None declared, Sandro Giannini: None declared, Andrea Giusti Grant/research support from: Abiogen Pharma, Consultant for: EffRx, Speakers bureau: Abiogen Pharma, Eli Lilly, AMGEN, Andrea Giustina: None declared, Stefano Gonnelli: None declared, Nazzarena Malavolta: None declared, Claudio Marcocci Grant/research support from: Shire, Speakers bureau: Shire and AbiogenPharma, Salvatore Minisola: None declared, Nicola Napoli: None declared, Ranuccio Nuti: None declared, Giovanni Passeri Grant/research support from: Abiogen Pharma and Chiesi Farmaceutici, Speakers bureau: Abiogen Pharma and Chiesi Farmaceutici, Maurizio Rossini: None declared, Luigi Sinigaglia: None declared, Francesco Vierucci: None declared, Davide Gatti Speakers bureau: Abiogen, Amgen, Janssen-Cilag, Mundipharma, Pfeizer